Сфера послуг у контексті сталого розвитку - Калініченко, О.О.; Мосійчук, І.В.; Пойта, І.О. (Економіка природокористування і охорони довкілля, 2013)
Розглянуто закономірності та сталі тенденції функціонування сфери послуг в умовах сталого розвитку. Проаналізовано основні фактори розвитку сфери послуг. Article devoted to the analysis of patterns and trends in the functioning of services in the context of sustainable development. The analysis of the main factors of development services. One of the main results of the transformation of the economy of Ukraine is some progress in the social sphere. At the same time among the most important social problems, the solution of which is on the agenda, took a significant problem of radical improvement of service sectors, including services.
Enormous role in the functioning of the system of economic relations in society plays the service sector. This area of social economy attracts attention of economists, is the object of constant study, theoretical research and practical bases the place and role of employees in the service of social reproduction. These studies are required to develop appropriate socio-economic policies of society in respect of services on a particular segment of social development.